HUBUNGAN ANTARA MARAH DAN KECEMASAN SETELAH MENGONSUMSI MINUMAN KOMBINASI MALTODEKSTRIN DAN VITAMIN C PADA ATLET SEPAK BOLA - Yuni Afriani; Noor Rochman Hadjam; Arta Farmawati (Medika Respati : Jurnal Ilmiah Kesehatan, 2015)
Backgrounds: Stress causes athletes to negative react and decreased the ability of the sport. Physical exercise can improve the ability either physiologically or psychologically, but lead to fatigue caused by dehydration and hypoglycemia. Fatigue is an aspect causes someone into negative mood and anxiety that influence the performance. Maltodextrin has a lower osmolarity and glycemic index than glucose used as a brain food, improve emotional and performance. Vitamin C as a cofactor of neurotransmitters and antioxidants can improve psychological conditions and support the performance of athletes.Methods: This research was a quasi experimental with same subject design. The subjects were 14 football student’s athlete. In the first treatment subjects received a drink of 15% maltodextrin and 250 mg of vitamin C in 300 ml, while in the second treatment, subjects received plain water given 5 minutes after the physical exercise. Measurement of anger and state anxiety will be done in 2 times; 5 minutes after physical exercise, and 15 minutes after drink.Results: There are a significant changes after consuming a combination drinks of maltodextrin and vitamin C on state anxiety (p<0,05) but no significant changes on anger (p>0,05). There are a significant correlation between anger and state anxiety after consumption a combination drink of maltodextrin and vitamin C.Conclusion: Maltodextrin and vitamin C has the potential effect to improve the state anxiety and correlate to anger in football athletes. Keywords: Maltodextrin, Vitamin C, Anger, State Anxiety, FootballNutrition Program, Faculty of Health Sciences, Universitas Respati YogyakartaDepartement of  Psychology Faculty of  Psychology, Universitas Gadjah MadaDepartement of  Biochemistry Faculty of  Medicine, Universitas Gadjah Mada